The interactive effect of flipped digital classrooms and student engagement on learning outcomes in social science education - Zen, Zelhendri; Reflianto, Reflianto; Ariani, Farida; Wandi, Joni Indra; Afnita, Nora (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study evaluates the effectiveness of the Flipped Digital Classroom (FDC) method in enhancing social science education by integrating digital-based learning through Google Classroom, Zoom Meeting, and social media. Using a quasi-experimental design, the study compares the FDC group, which received technology-based flipped learning, with a control group that followed a conventional lecture approach. The results indicate that the FDC method significantly improves students' social science learning outcomes, with an average score of 73.49 compared to 67.72 in the control group (p = 0.0). Student engagement, measured through behavioral, emotional, and cognitive aspects, also positively contributes to learning outcomes, particularly among students with high engagement levels. These findings confirm that FDC has the potential to revolutionize social science education by enhancing student engagement and achievement. Therefore, it is recommended that educators implement FDC and that schools support it with adequate training and technological infrastructure.